2004
DOI: 10.2337/diacare.27.5.1153
|View full text |Cite
|
Sign up to set email alerts
|

Natural Progression of Diabetic Peripheral Neuropathy in the Zenarestat Study Population

Abstract: OBJECTIVE -The aim of this study was to report the baseline and natural progression of diabetic peripheral neuropathy over 12 months in a large mild-to-moderate neuropathy population.RESEARCH DESIGN AND METHODS -Patients from a multicentered trial of zenarestat, an aldose reductase inhibitor, had serial measures of neurologic function, including nerve conduction studies (NCSs), quantitative sensory testing (QST), and clinical neuropathy rating scores at baseline and at 12 months. Baseline population descriptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 19 publications
3
43
1
4
Order By: Relevance
“…Similar to our patients, reduction of amplitudes was shown to be more marked in lower limb nerves. In general, nerve conduction declined in all nerves tested, with the decline in sural sensory conduction velocity achieving statistical significance 10 . Sensory nerve action potential amplitude is reduced by up to 60% in the legs 11 .…”
Section: Discussionmentioning
confidence: 87%
“…Similar to our patients, reduction of amplitudes was shown to be more marked in lower limb nerves. In general, nerve conduction declined in all nerves tested, with the decline in sural sensory conduction velocity achieving statistical significance 10 . Sensory nerve action potential amplitude is reduced by up to 60% in the legs 11 .…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, HbA 1c levels at baseline were less than 7.0% in 50% of our subjects, whereas patients with good glycemic control were excluded in the zenarestat study. Furthermore, the other factors may have greater effects, because a clinical study (Brown et al, 2004) has demonstrated that the changes of nerve function test results during 12 months were independent of baseline HbA 1c stratification in a large diabetic peripheral neuropathy population. It has been speculated that the ability to improve or preserve nerve function may be limited by disease severity ).…”
Section: Discussionmentioning
confidence: 99%
“…Greene et al (9) reported a decline in peroneal motor NCV and median and sural sensory NCV of Ͼ0.25 m/s in the placebo-treated patients in a zenarestat study. Brown et al (10) reported more detail on these same patients, indicating a decline of median forearm sensory NCV of Ϫ0.05 m/s (n ϭ 360), of peroneal motor NCV of Ϫ0.2 m/s (n ϭ 359), and of sural CV of Ϫ0.65 m/s (n ϭ 359) in 12 months. Other authors (11,12) have reported deterioration in NCV in patients with DSP.…”
Section: Safetymentioning
confidence: 77%